Domestic violence: repercussions for women and children - Jordana Brock Carneiro; Nadirlene Pereira Gomes; Fernanda Matheus Estrela; Jéssica Damasceno de Santana; Rosana Santos Mota; Alacoque Lorenzini Erdmann (Universidade Federal do Rio de Janeiro, 2017)
Abstract Objectives: To know the meanings attributed by women regarding the repercussions of the experience of domestic violence. Method: Qualitative study, based on the Grounded Theory method. Data were collected in two sticks of domestic and family violence against the Brazilian Northeast woman. An interview was conducted with 37 participants, who composed two sample groups. Results: The study demonstrates that the physical and mental health of women and their children are compromised, expressed through visible marks such as bruises and cuts, in addition to low self-esteem, sadness, fear and depression. There are also repercussions for the social relations of women as a consequence of social isolation and non-qualification for the labor market, and of children, related to the decrease in school performance, introspection and vulnerability to drug use. Conclusion: It is necessary to sensitize health professionals to the recognition of cases and promote educational actions, thus transcending the invisibility barrier of domestic violence.